Militarization and democracy in West Germany's border police, 1951-2005 - Livingstone, David M. (German history in context, 2024)
"A social history of West Germany's Bundesgrenzschutz (BGS, Federal Border Police) that complicates the telling of the country's history as a straightforward success story. The 2020 murder of George Floyd by Minneapolis police officers shows that police violence is still a problem in Western democracies. Floyd's murder prompted some critics to hail the German police as a model of democratic policing that should be emulated. After 1945, Germany's police forces had supposedly shed the militarization and authoritarian impulses still prevalent in other nations' forces. These uncritical appraisals, however, deserve closer analysis. This book is a social history of West Germany's Bundesgrenzschutz (BGS), a federal border guard established in 1951 that became re-unified Germany's first national police force. It argues that the BGS revived authoritarian traditions of militarized policing and kept them alive long into the postwar era even though the country was supposedly consigning these problematic legacies to its past. The BGS was staffed and led by Wehrmacht and SS veterans until the late 1970s, and while West Germany was democratizing, BGS commanders were still planning to fight wars and were teaching its officers "street fighting" tactics. While the end outcome was positive, the study contributes to the growing body of recent research that complicates the writing of the Federal Republic's history as a "success story." Dealing explicitly with post-fascist West Germany's struggle to establish a democratic police force, the book enters a conversation with studies concerned with democratization, security, and Germany's effort to overcome its Nazi past. DAVID M. LIVINGSTONE holds a PhD in History from the University of California-San Diego. He is retired as Chief of Police of Simi Valley, California and is an adjunct professor at California Lutheran University"--